Determination of the Charge per Micro-Bunch of a Self-Modulated Proton Bunch using a Streak Camera. (July 2020) - Bachmann, A.-M.; Muggli, P.
Abstract: The Advanced Wakefield Experiment (AWAKE) develops the first plasma wakefield accelerator with a high-energy proton bunch as driver. The 400 GeV bunch from CERN Super Proton Synchrotron (SPS) propagates through a 10 m long rubidium plasma, ionized by a 4TW laser pulse co-propagating with the proton bunch. The relativistic ionization front seeds a self-modulation process. The seeded self-modulation transforms the bunch into a train of micro-bunches resonantly driving wakefields. We measure the density modulation of the bunch, in time, with a streak camera with picosecond resolution. The observed effect corresponds to alternating focusing and defocusing fields. We present a procedure recovering the charge of the bunch from the experimental streak camera images containing the charge density. These studies are important to determine the charge per micro-bunch along the modulated proton bunch and to understand the wakefields driven by the modulated bunch.